Iodine bioavailability from cow milk: a randomized, crossover balance study in healthy iodine-replete adults. Issue 1 (1st July 2019) - van der Reijden, Olivia L; Galetti, Valeria; Bürki, Sarah; Zeder, Christophe; Krzystek, Adam; Haldimann, Max; Berard, Joel; Zimmermann, Michael B; Herter-Aeberli, Isabelle
ABSTRACT: Background: Milk and dairy products are considered important dietary sources of iodine in many countries. However, to our knowledge, iodine bioavailability from milk has not been directly measured in humans. Objective: The aim of this study was to compare iodine bioavailability in iodine-replete adults from: 1 ) cow milk containing a high concentration of native iodine; 2 ) milk containing a low concentration of native iodine, with the addition of potassium iodide (KI) to assess a potential matrix effect; and 3 ) an aqueous solution of KI as a comparator; with all 3 containing equal amounts of total iodine (263 µg/250 mL). We also speciated iodine in milk. Design: We conducted a 3-wk, randomized, crossover balance study in adults ( n  = 12) consuming directly analyzed, standardized diets. During the 3 test conditions — high intrinsic iodine milk (IIM), extrinsically added iodine in milk (EIM), and aqueous iodine solution (AIS) — subjects collected 24-h urine over 3 d and consumed the test drink on the second day, with 3- or 4-d wash-out periods prior to each treatment. Iodine absorption was calculated as the ratio of urinary iodine excretion (UIE) to total iodine intake. Milk iodine speciation was performed using ion chromatography-mass spectrometry. Results: Iodine intake from the standardized diet was 195 ± 6 µg/d for males and 107 ± 6 µg/d for females; the test drinks provided an additional 263 µg. Eleven subjects completed the protocol. There was a linear relation between iodine intake and UIE (β = 0.89, SE = 0.04, P  < 0.001). There were no significant differences in UIE among the 3 conditions ( P  = 0.24). Median (range) fractional iodine absorption across the 3 conditions was 91 (51–145), 72 (48–95), and 98 (51–143)% on days 1, 2, and 3, respectively, with day 2 significantly lower compared with days 1 and 3 ( P  < 0.001). In milk, 80–93% of the total iodine was inorganic iodide. Conclusion: Nearly all of the iodine in cow milk is iodide and although fractional iodine absorption from milk decreases with increasing dose, its bioavailability is high. The trial was registered at clinicaltrials.gov as NCT03590431.